1984
DOI: 10.1227/00006123-198412000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Avulsion of the Brachial Plexus

Abstract: The author reviews the diagnosis and treatment of avulsion injuries of the brachial plexus. He discusses the nature of the pain and the use of transcutaneous nerve stimulation for its relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
9

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 0 publications
2
25
0
9
Order By: Relevance
“…These data are consistent with classic observations (23,27) and may account for some of their therapeutic specificities, particularly the good efficacy of surgical procedures (e.g. dorsal root entry zone lesions) for pain paroxysms in plexus avulsion (33).…”
Section: Discussionsupporting
confidence: 89%
“…These data are consistent with classic observations (23,27) and may account for some of their therapeutic specificities, particularly the good efficacy of surgical procedures (e.g. dorsal root entry zone lesions) for pain paroxysms in plexus avulsion (33).…”
Section: Discussionsupporting
confidence: 89%
“…45 Brachial plexus avulsion pains have been dichotomized into either continuous, often burning or throbbing pain and likely involving thalamic neuroplasticity, or shooting paroxysms associated with dorsal horn hyperactivity. 48,49 Both phantom limb pain after amputation and deafferentation pain after BPA fulfill a recently revised definition of neuropathic pain as pain caused by a lesion or disease of the somatosensory system. 27 Neuropathic pain symptom severity and duration are often greater than other forms of chronic pain, leading patients and clinicians to consider neurosurgery.…”
mentioning
confidence: 99%
“…Similarly, milder pain is related by patients who underwent operative reconstruction of the BP, even by those in whom root avulsion was managed by the use of intercostal nerves as new sources of neurotization of the PN's of the upper extremity, and showed satisfactory motor and sensory return. Some authors regard pain as one of the major problems of patients with BP injuries [36]. Our experience up to now has shown that there is an inverse ratio between pain in the affected upper limb and functional restoration, occurring spontaneously or achieved by microsurgical repair.…”
Section: Personal Experiencementioning
confidence: 85%